(untitled) (Training and Practice : Journal of Educational Sciences, 2011)
Katalin Hajdicsne Varga describes the recent situation of so called management teacher training in her two papers in English and Russian, which is a special field of teacher education, from points of view of its development, history and from the point of view of its specific features, as well. [Published in H. Varga Katalin (2011): Beszéd- és szövegrögzítés. Töréteneti áttekintés és helyzetkép. Kaposvár, pp 87–98.]